A robust method for assessing mitochondrial function in healthy and diseased frozen cardiac tissue - Liangyu Hu; Alexia van Rinsum; Rocco Caliandro; Xi Qi; Shuxiu Fan; Xinyi Jiang; Jur Massop; Melissa Bekkenkamp-Grovenstein; Christiane Ott; Tilman Grune; Melissa A. E. van de Wal; Werner J. H. Koopman; et al. (Communications Biology)
Abstract Cardiovascular diseases are often associated with impairment in mitochondrial function. However, existing respirometry measuring mitochondrial function are limited by the necessity of fresh tissue samples. This study develops a method with tailored substrate-inhibitor titration (TSIT) of mitochondrial electron transport complexes (ETC) to measure mitochondrial function in frozen cardiac samples using high-resolution respirometry. Briefly, acetyl-CoA is added to fuel the tricarboxylic acid (TCA) cycle for NADH production, enabling complex I (CI)-linked respiratory assessment. NADH is then added to measure maximum CI-linked respiratory capacity, followed by rotenone and succinate to assess complex II (CII)-linked respiratory capacity. TSIT detects mitochondrial functional differences between frozen atrial and ventricular tissue, with comparable results as measured in fresh samples. It also detects cardiac mitochondrial dysfunction across various (patho)physiological mouse models and in human frozen cardiac samples, highlighting its clinical potential. Furthermore, we provides the first evidence for SC formation between the ETC-SCs and the TCA cycle metabolon using blue native electrophoresis, underpinning why TSIT is feasible in frozen tissue. In conclusion, we establish a novel, robust, sensitive and translational method (TSIT) for assessing mitochondrial (dys)function in frozen cardiac samples from various species, enabling flexible analysis of mitochondrial function in both laboratory and clinical settings.